DEVELOPMENT OF GAME-BASED MATHEMATICS STUDENTS’ WORKSHEETS INTEGRATED WITH LOCAL WISDOM - Raupu, Sumardin; Utari, Dian; Nursyamsi, Nursyamsi; Marwiyah, St. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to determine the validity of procedures for developing game-based math students’ worksheets that are integrated with local wisdom. The type of research is called Research and Development (R&D) with reference to the ADDIE model with five development steps, namely Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SMP Negeri 2 Burau with the research subjects of the seventh grade students. To find out the product validity, the researchers distributed a questionnaire to the material experts, media experts, and teachers. The results showed that the worksheet category was valid for use in learning, including the assessment of material experts (80.4%) in the valid category, media experts (91.3%) in the very valid category, and subject teachers (82.6%) in the valid category. The game-based worksheets can be implemented by utilizing them as supporting media for integer material and supporting the creation of a conducive atmosphere. Abstrak: Penelitian ini bertujuan untuk mengetahui prosedur validitas pengembangan LKS matematika berbasis games method diintegrasikan dengan kearifan lokal. Jenis penelitian ini adalah Research and Development (R&D) dengan mengacu pada model ADDIE dengan lima langkah pengembangan yaitu Analyze, Design, Development, Implementation, and Evaluation. Penelitian dilakukan di SMP Negeri 2 Burau dengan subjek penelitian yaitu siswa kelas VIII. Untuk mengetahui kelayakan produk, peneliti menyebar angket kepada ahli materi, ahli media, dan guru mata pelajaran. Hasil penelitian menunjukkan bahwa LKS termasuk kategori valid untuk digunakan dalam pembelajaran dilihat dari penilaian ahli materi (80.4%) dengan kategori valid, ahli media (91.3%) kategori sangat valid, guru mata pelajaran (82.6%) kategori valid. LKS berbasis games method dapat diimplementasikan dengan dimanfaatkan sebagai media pendukung pada materi bilangan bulat dan mendukung terciptanya suasana kondusif.